Equilibrium in Search Models with Adverse Selection - James W. Albrecht; Susan B. Vroman (The Research Institute of Industrial Economics (IUI), 1990)
This paper examines the problem of nonexistence of equilibrium in a simple search model with asymmetric information. A pure-strategy, symmetric Nash equilibrium fails to exist because adverse selection arising from steady-state considerations causes a nonconcavity in the payoff function.
Keywords: D82; J64; 330; Nash equilibria; Informational asymmetry; Search model